The Speed of Increasing milk Feeds: a randomised controlled trial. Issue 1 (December 2017) - Abbott, Jane; Berrington, Janet; Bowler, Ursula; Boyle, Elaine; Dorling, Jon; Embleton, Nicholas; Juszczak, Edmund; Leaf, Alison; Linsell, Louise; Johnson, Samantha; McCormick, Kenny; McGuire, William; et al.
Abstract Background In the UK, 1–2% of infants are born very preterm (<32 weeks of gestation) or have very low birth weight (<1500 g). Very preterm infants are initially unable to be fed nutritional volumes of milk and therefore require intravenous nutrition. Milk feeding strategies influence several long and short term health outcomes including growth, survival, infection (associated with intravenous nutrition) and necrotising enterocolitis (NEC); with both infection and NEC being key predictive factors of long term disability. Currently there is no consistent strategy for feeding preterm infants across the UK. The SIFT trial will test two speeds of increasing milk feeds with the primary aim of determining effects on survival without moderate or severe neurodevelopmental disability at 24 months of age, corrected for prematurity. The trial will also examine many secondary outcomes including infection, NEC, time taken to reach full feeds and growth. Methods/design Two thousand eight hundred very preterm or very low birth weight infants will be recruited from approximately 30 hospitals across the UK to a randomised controlled trial. Infants with severe congenital anomaly or no realistic chance of survival will be excluded. Infants will be randomly allocated to either a faster (30 ml/kg/day) or slower (18 ml/kg/day) rate of increase in milk feeds. Data will be collected during the neonatal hospital stay on weight, infection rates, episodes of NEC, length of stay and time to reach full milk feeds. Long term health outcomes comprising vision, hearing, motor and cognitive impairment will be assessed at 24 months of age (corrected for prematurity) using a parent report questionnaire. Discussion Extensive searches have found no active or proposed studies investigating the rate of increasing milk feeds. The results of this trial will have importance for optimising incremental milk feeding for very preterm and/or very low birth weight infants. No additional resources will be required to implement an optimal feeding strategy, and therefore if successful, the trial results could rapidly be adopted across the NHS at low cost. Trial registration ISRCTN Registry;ISRCTN76463425 on 5 March, 2013.